Nutritional quality and antioxidant activity of wheatgrass (Triticum aestivum) unwrap by proteome profiling and DPPH and FRAP assays - Parit, Santosh B.; Dawkar, Vishal V.; Tanpure, Rahul S.; Pai, Sandeep R.; Chougale, Ashok D. (Journal of Food Science, 2018)
Precious contribution of plants in the field of medicine is very well known. Wheat (Triticum aestivum) seeds and seedlings are an important source of food and feed due to the presence of various health-promoting compounds. Proteomic analysis of three seed developmental stages (0, 8, and 16 days after germination [DAG]) of wheat was carried out using liquid chromatography-mass spectrometry. A total of 297 proteins were identified and their functional annotation revealed that a majority of them were involved in preventing many diseases, oxidative stress, primary metabolism, storage, and energy related mechanisms. Particularly to mention, peroxidases, superoxide dismutases, and cytochromes are abundantly present in wheatgrass. In the ferric-reducing antioxidant power assay, antioxidant activity was increased by 1.55 times after 16 DAG as compared to 0 DAG, however it was decreased after 8 DAG. The antioxidant activity of the plant extracts by DPPH had an increasing trend after all the three time points. The percent radical scavenging activity of extract by DPPH was 15, 22, and 30 after 0, 8, and 16 DAG, respectively. Observations obtained revealed that antioxidant power of the plants is directly proportional to the age of seedlings. Data attained on wheatgrass showing that it can be a strong antioxidant agent due to its free radical scavenging activity and could be used in stress and nourishing human health. Practical ApplicationWheatgrass contains minerals, phytochemicals, active enzymes, and vitamins that can be easily absorbed. The consumption of wheatgrass juice can give better health benefits. Information about beneficial properties of wheat grass juice is clearly mentioned in this work.Proteins found in wheatgrass are known to be involved in preventing many diseases, oxidative stress, primary metabolism, storage, and energy-related mechanisms. Results of this work revealed that Triticum aestivum seedlings can act as an antioxidant agent due to their free radical scavenging activity and can be constructive to control or treat many health complications. From all these results we believed that wheatgrass can be used for the nourishment of humans.
Keywords: Antioxidant; LC-MSE; peroxidase; proteomics; Triticum aestivum; wheatgrass